2010
DOI: 10.1111/j.1750-3841.2010.01580.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liberibacter Infection (Huanglongbing or “Greening” Disease) of Citrus on Orange Juice Flavor Quality by Sensory Evaluation

Abstract: Assumptions that juice made from oranges harvested from Huanglongbing (from infection with Liberibacter sp.) affected trees is off-flavored appeared to be generally more true for Hamlin juice than for Midsweet or Valencia, especially for Hamlin juice made from symptomatic fruit. For Midsweet and Valencia, flavor differences between juice made from fruit harvested from diseased or healthy trees varied greatly between trees, season, and even processing method. Under a commercial processing situation, where juice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(98 citation statements)
references
References 27 publications
1
91
1
5
Order By: Relevance
“…Early reports of juice quality impacts indicated that juice from HLB fruit was bitter and had numerous off-flavours (McClean and Schwartz, 1970; daGraça, 1991; Stokstad, 2006). Juice of symptomatic mature fruit was lower in juice percentage, °Brix, and °Brix/% acid ratio, and higher in acidity compared with asymptomatic and healthy fruit (Dagulo et al , 2010; Plotto et al , 2010). Such a juice profile is similar to that of immature fruit.…”
Section: Introductionmentioning
confidence: 86%
“…Early reports of juice quality impacts indicated that juice from HLB fruit was bitter and had numerous off-flavours (McClean and Schwartz, 1970; daGraça, 1991; Stokstad, 2006). Juice of symptomatic mature fruit was lower in juice percentage, °Brix, and °Brix/% acid ratio, and higher in acidity compared with asymptomatic and healthy fruit (Dagulo et al , 2010; Plotto et al , 2010). Such a juice profile is similar to that of immature fruit.…”
Section: Introductionmentioning
confidence: 86%
“…Fruit were cleaned with JBT Fruit Cleaner 395, and juiced using a fresh juicer (JBT Fresh’n Squeeze ® Point-of-Sale Juicer, JBT FoodTech Corporation, Lakeland, FL, USA). Unfortunately, citrus greening or Huanglongbing (HLB) disease, associated with Liberibacter asiaticus ( C Las), had spread throughout the major citrus producing regions in Florida by 2010 [17], and the diseased fruit were shown to be associated with off-flavor and other negative quality defects [18,19]. Therefore, to eliminate this potentially complicating factor, the trees or fruit juice was tested for the disease before sampling.…”
Section: Methodsmentioning
confidence: 99%
“…A study from our laboratory looked at the Alpha MOS e-nose with 18 sensors, for ability to separate orange juice from fresh squeezed oranges, orange juice from a simulated commercial process (including pasteurization), orange juice from fruit harvested from healthy trees and the same commercially processed juice made from fruit harvested from Huanglongbing (HLB) infected trees and fresh squeezed tangerine juice (Figure 1). The e-nose separated all these juices using PCA, even the juice from HLB-infected trees, which were shown to have fruit that have off-aroma and a bitter-metallic flavor [42,43]. …”
Section: E-nosesmentioning
confidence: 99%